2011
DOI: 10.1172/jci41062
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine reduces the size and activity of von Willebrand factor in human plasma and mice

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a life-threatening disease characterized by systemic microvascular thrombosis caused by adhesion of platelets to ultra-large vWF (ULVWF) multimers. These multimers accumulate because of a deficiency of the processing enzyme ADAMTS13. vWF protein forms long multimers from homodimers that first form through C-terminal disulfide bonds and then join through their N termini by further disulfide bonding. N-acetylcysteine (NAC) is an FDA-approved drug that has long been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(200 citation statements)
references
References 42 publications
8
191
0
1
Order By: Relevance
“…As our platform matures, we anticipate that μVNs can be used to test drugs and drug-delivery strategies that target microvascular function (for example, angiogenesis (47) and hypertension) (48) or blood-endothelium interactions (for example, sickle cell disease (49) and thrombotic thrombocytopenic purpura) (50). Scaffolds with μVNs could also provide a starting point for the growth of vascularized tissues in vitro for applications in regenerative medicine (51).…”
Section: Discussionmentioning
confidence: 99%
“…As our platform matures, we anticipate that μVNs can be used to test drugs and drug-delivery strategies that target microvascular function (for example, angiogenesis (47) and hypertension) (48) or blood-endothelium interactions (for example, sickle cell disease (49) and thrombotic thrombocytopenic purpura) (50). Scaffolds with μVNs could also provide a starting point for the growth of vascularized tissues in vitro for applications in regenerative medicine (51).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, administration of NAC to ADAMTS13-deficient mice reduces plasma vWF multimers and leads to rapid resolution of thrombi. 25 Recently, the use of NAC as adjunctive treatment in a patient with refractory TTP was apparently efficient. 26 However, some failures were also reported.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…It replenishes hepatic glutathione depleted by drug conjugation [25]. Recently, clinical studies reported its potential antioxidant activity in protection against contrast induced nephropathy [26] and thrombosis [27]. Also, it has anti-inflammatory properties reported in several tissues like in cerebral and pulmonary inflammation [28,29].…”
Section: Introductionmentioning
confidence: 99%